ChemInform Abstract: Convenient Methods for the Synthesis of Chiral Amino Alcohols and Amines. Issue 22 (13th May 2013) - Periasamy, Mariappan; Gurubrahamam, Ramani; Sanjeevakumar, Nalluri; Dalai, Manasi; Alakonda, Laxhmaiah; Reddy, Polimera Obula; Suresh, Sundaram; Satishkumar, Sakilam; Padmaja, Meduri; Reddy, Meda Narsi; et al., et al.
Abstract Review: 132 refs.